(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Pot experiments wereconducted in 2021at the screen house to evaluate the effect of nitrogen, phosphorus and potassium (NPK) and poultry manure (PM) rates on the growth and yield of soybean (TGx1835-10E). The treatments consisted of Nitrogen Phosphorus and Potassium (NPK 15:15:15) rates (0g, 0.6g, 1.2g and 2.4g) and Poultry Manure (PM) rates (0g, 3g, 6g and 12g) which were combined in factors to give sixteen treatment combinations and Control with neither fertilizer. The experiment was laid out in a completely randomized design and replicated six times.Soil and PM were analyzed for physico-chemical parameters using standard procedures for pH, O.C, O.M, P, N, Na, Ca, Mg, K, EC and particle size distribution. Data collected includes; growth performance at 64 days after planting (DAP) for; plant height, root length, number of leaves, number of branches, chlorophyll content, leaf area, shoot dry weight) and yield attributes (number of pods/plant, number of seeds/pod, economical yield, biological yield, harvest index) and these data were subjected to analysis of variance (ANOVA) and means were separated using Tukey. Result indicated that the combined application of PM and NPK significantly (p<0.05) increased plant height, number of leaves, number of branches, leaf area, chlorophyll content, shoot dry weight, harvest index and economic yield of soybeanthan the sole application of either PM or NPK and the control. No significant difference was however recorded for number of pods, number of seeds and biological yield. The use of balanced doses of inorganic and organic fertilizers improved growth and yield qualities of soybean.